Organizational Learning Curves: A Method for Investigating Intra-Plant Transfer of Knowledge Acquired Through Learning by Doing - Epple, Dennis; Argote, Linda; Devadas, Rukmini (Organization Science, 1991)
This paper illustrates how a learning-curve model can be generalized to investigate potential explanations of organizational learning. The paper examines the hypothesis that knowledge acquired through by learning by doing is embodied in an organization's technology by analyzing the amount of transfer that occurs across shifts within a plant. If knowledge becomes completely embodied in technology, transfer across shifts should be complete since both shifts use the same technology. Methods that can be used for studying intra-plant transfer of knowledge are presented. The methods are illustrated by analyzing data from a plant that began production with one shift and then added a second shift several months into the production program. Three aspects of transfer are analyzed: (1) carry forward of knowledge when the plant makes the transition from one to two shifts, (2) transfer across shifts after both shifts are operating, and (3) transfer across time. Results indicate that substantial, but less than complete, transfer of knowledge occurred when the second shift was introduced. Once both shifts were operating, partial transfer across them occurred. Implications of the results for a theory of organizational learning and practical applications are discussed.